EFFORTS TO PREVENT THE SPREAD OF COVID-19 ACCORDING TO THE DOCTRINE OF MUHAMMADIYAH IN INDONESIA: HADITH STUDIES - Rohmansyah, Rohmansyah; Hidayat, Yayat (Islam Futura, 2024)
COVID-19 has emerged as the global challenge confronting the community. The Indonesian government and Muhammadiyah have been engaged in efforts to mitigate the ongoing transmission of COVID-19. Diverse strategies have been employed to combat this disease and prevent its spread and fatalities. This study aims to examine and explain Muhammadiyah’s preventive efforts in Indonesia to combat COVID-19, drawing upon an interpretation of hadiths from the Prophet. A qualitative method was employed to address this issue with a historical, sociological approach to investigate the social conditions during the time of the Prophet and their prevention in relation to contemporary times performed by Muhammadiyah. The study revealed that Muhammadiyah has addressed community and humanitarian issues by implementing efforts to prevent the spread of COVID-19. One such effort was restricting worship activities in mosques and encouraging people to perform them at home until the situation returned to normal. However, in areas deemed safe from COVID-19, worship could still be conducted in mosques while adhering to health protocols such as maintaining social distance, wearing masks, and practicing proper hand hygiene. Furthermore, learning in large group settings has been limited, leading to a shift toward remote online learning from home. Engaging in outdoor muamalah activities, such as working, meetings, religious studies, shopping, and other activities that attract and result in big gatherings, has also been restricted. These efforts aim to disrupt the transmission of COVID-19 as a manifestation of societal care, guided by the teachings of the Prophet as recorded in the hadiths.